PENGARUH LINTANG DAN BUJUR TEMPAT TERHADAP PENENTUAN AWAL WAKTU SALAT SUBUH MASJID-MASJID DI KECAMATAN KALAENA KABUPATEN LUWU TIMUR - Adelin, Weliana; B, Halimah (Universitas Islam Negeri Alauddin Makassar, 2025)
Abstract The importance of holding prayers according to predetermined times, and detailing how prayer times are arranged based on the guidelines of the Qur'an and the hadith of the Prophet, determining prayer times based on geographical factors, especially latitude and longitude, is a major concern, considering the impact on the implementation of worship. The type of research used is field research with a syar'i and astronomy research approach. Equipped with primary and secondary data. Processing and analysis of data through the process of data reduction, data editing and data transformation. The research results obtained, among others, are that there are several bases used in determining the initial time for the dawn prayer for mosques in the Kalaena District which causes a difference in the start time for the dawn prayer. The latitude and longitude of the place have an effect of 0.42 seconds to 7.52 seconds on determining the initial time for the morning prayers for mosques in the Kalaena District, East Luwu Regency. The causes of the difference in the early dawn prayer time of the mosques in the Kalaena District include differences in the references used by the mosques in the Kalaena District, Muadzin, Ihtiyath and the digital clock used. It is hoped that this research can answer questions that arise in the community about the early morning prayer time.